Centralisation of post-resuscitation care after out-of-hospital cardiac arrest at heart centres - a nationwide follow-up study. (3rd May 2023) - Rasalingam Mork, S; Gregers, E; Kragholm, K; Kjaergaard, J; Folke, F; Torp-Pedersen, C; Kober, L; Boas Soja, A M; Juhl Terkelsen, C; Michalik, F; Eifer Moller, J; Lund Henriksen, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Recent guidelines recommend centralisation of post-resuscitation care in out-of-hospital cardiac arrest (OHCA) patients in dedicated Cardiac Arrest Centres (CACs) aiming to improve outcome. Purpose: To describe the process of implementation of the centralisation policy and impact on 30-day mortality rate. Methods: This nationwide study included all adult OHCA patients (>18 years) based on the Danish Cardiac Arrest Registry. Centralisation was introduced in 2009, 2010, and 2012 in four regions (A, B, C, D), and one region has not yet implemented the policy (control). Parallel trends assumption was made and a difference-in-difference model with repeated cross-sections was used to estimate the average treatment effect on the treated patients. The 30-day mortality was compared between patients living in regions that introduced centralisation versus control region without centralisation. Results: A total of 20, 566 patients with OHCA were identified between 2007 and 2020. The majority were between 50 to 75 years (53.7%) and 67.8% male. Bystander cardiopulmonary resuscitation was performed in 55.3%. Shockable rhythm was present in 34.6% of the patients. The policy of centralisation of OHCA in CACs has been gradually and not yet completely implemented (Figure 1A). Patients with shockable rhythms (72%), and younger patients < 50 years (64%) were more frequently transported to CACs. The 30-day mortality was lower among patients transported to CACs (Figure 1B). Centralisation significantly improved survival by 6% (95% CI: 2%-10%) percentage points compared to the control region after controlling for all known covariates (sex, age, Charlson Comobidity Index, shockable rhythm, and bystander cardiopulmonary resuscitation). Conclusions: In this nationwide study, centralisation of post-resuscitation care of OHCA in dedicated CACs has been gradually implemented over time. Although, OHCA patients with favorable prognostic factors were more frequently transported to CACs, centralisation increased survival by 6 absolute percentage points.